Ons sal antwoord op jou roepstem - Chris Broodryk (Communicare)
This article argues that Steve Hofmeyr’s Afrikaner identity, an identity he performs across various media platforms, including a selection of feature length Afrikaans films, is a paradoxical hybrid of Afrikaner exceptionalism and claims to victimhood. The exceptionalism and self-imposed victimhood are engaged in an across-media dialogue, as Steve Hofmeyr’s social media and political activist persona speak to his participation in three Afrikaans language films: Pretville (Korsten, 2012), Platteland (Else, 2011) and Treurgrond (Roodt, 2015). Hofmeyr’s presence foregrounds and exacerbates an already problematic ideological context in which attempts at multiculturalism are rendered moot by the conservatism in these films, especially where land – the farm – is concerned. While Pretville invents a 1950s South African town that fails to correspond to any inhabited reality of that time, Platteland offers an Afrikaans musical-western wherein Hofmeyr dominates as patriarch. Finally, the attempts of Treurgrond at raising farm murder awareness are nullified through casting Hofmeyr as a farmer facing a land claim, given Hofmeyr’s active campaigning against an alleged Boer genocide.